POTENTIAL OF AQUEOUS OZONE FOR THE IN VITRO STERILIZATION PROCEDURE OF SOLANACEAE - YULIANA, TITIS; PRIHASTANTI, ERMA; NURCHAYATI, YULITA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This research aimed to verify the use of aqueous ozone as an alternative sterilizer for in vitro sterilization procedure. Methods: Three species of Solanaceae were selected based on their trichomes. They are thorn apple (Datura metel L.), eggplant (Solanum melongena), and tomato (Lycopersicon pimpinellifolium). The treatment used four levels of concentrations; K0 (NaOCl – control), K1 (AO 0.1 ppm), and K2 (AO 0.5 ppm), K3 (1 ppm) and it employed three types of leaves, namely, D1 (thorn apple), D2 (eggplant), and D3 (tomato). The data were analyzed by analysis of variance univariate two factors and followed by Duncan’s multiple comparisons test. Results: This assay showed that the effect of ozone was almost immediately against microorganisms, and the optimum ozone concentration depends on the types of the leaf. Both levels of ozone concentration and types of leaves had a significantly different effect (p<0.05), and there is no interaction between aqueous ozone concentration and types of leaves (p>0.05). The level of sterility in K0 is 77, 78%, K1 is 22, 22%, K2 is 44, 44%, and K3 is 100%. Ozone 1 ppm had the highest result, but there is no viable explant because they got damage in their cells. Conclusions: Aqueous ozone showed good potential to inhibit the growth of microorganisms for the in vitro sterilization procedure of Solanaceae.